2007
DOI: 10.1080/01490400600983446
|View full text |Cite
|
Sign up to set email alerts
|

Expanding, Reducing, Concentrating and Diffusing: Post Retirement Leisure Behavior and Life Satisfaction

Abstract: This study examined patterns of continuity and change in leisure behavior of recently retired individuals. The study investigated post-retirement leisure behavior in an Israeli national sample. It explored the differences among four defined groups: reducers, concentrators, diffusers and expanders, and measured their leisure participation and life satisfaction. Results indicated that the expanders and the concentrators enjoyed a significantly higher life satisfaction. The findings supported activity theory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…While continuity theory emphasizes the maintenance of activities, innovation theory promotes innovation as a means of preserving identity and adaptation, evidenced when people add new leisure activities later in life (self-invention innovation) or continue with earlier interests (self-preservation innovation) (Nimrod, 2007a(Nimrod, , 2007bNimrod & Kleiber, 2007). The latter most closely overlaps with continuity theory (Atchley, 1999).…”
Section: Models Of Activity Engagement and Retirement Adjustmentmentioning
confidence: 95%
“…While continuity theory emphasizes the maintenance of activities, innovation theory promotes innovation as a means of preserving identity and adaptation, evidenced when people add new leisure activities later in life (self-invention innovation) or continue with earlier interests (self-preservation innovation) (Nimrod, 2007a(Nimrod, , 2007bNimrod & Kleiber, 2007). The latter most closely overlaps with continuity theory (Atchley, 1999).…”
Section: Models Of Activity Engagement and Retirement Adjustmentmentioning
confidence: 95%
“…As a result, greater attention has been focused on providing recreation opportunities for individuals with disabilities using a variety of service delivery approaches (Hutchison & Lord, 1979;Hutchison & McGill, 1992, 2007. A current disability is an important factor to consider when researching leisure behavior given that adaptive strategies and a willingness to pursue integrative programming among leisure service providers is often necessary to achieve the full inclusion and participation of individuals with disabilities (Kennedy, Smith, & Austin, 1991).…”
Section: Downloaded By [Central Michigan University] At 09:41 19 Novementioning
confidence: 99%
“…Leisure repertoire is a concept with demonstrated utility in leisure research and has been defined as the number of different activities individuals engage in during their leisure time (Searle & Brayley, 2000). Existing research has demonstrated that leisure diversity may contribute to positive outcomes in the lives of individuals by reducing delinquency and anti-social behavior (Winther, 1989) and alleviating boredom in one's leisure time, while contributing to increased life-satisfaction (Iso-Ahola & Weissinger, 1990;Weissinger, Caldwell, & Bandalos, 1992), particularly among older adults (Nimrod, 2007). The work of Granovetter (1973) further suggests that broad leisure involvements may contribute to diverse weak ties that contribute to social capital by providing access to information and resources that are not readily available through one's immediate friends and family.…”
Section: Introductionmentioning
confidence: 98%
“…Continuity Theory (Atchley, 1989) was later developed to, in part, address criticisms of Activity Theory, including its inability to accommodate the changing competencies and preferences of older adults. Rather than simply contending that more activity equates to greater well-being, Continuity Theory proposes that people maintain well-being during late adulthood, and across transitions like retirement, by maintaining stability in the roles, behaviours and activities that have always given meaning to their lives (for discussion, see Nimrod, 2007aNimrod, , 2007b. That is, well-being is not dependent on the amount of activity in which people engage, but on the qualities of this activity and/or whether they are consistent with the individuals' existing structures and preferences.…”
Section: Introductionmentioning
confidence: 99%